Through the Valley of the Shadow of Death - Surviving the Dreaded Ebola Disease - Adaora Chinenye Okoli-Igonoh (Health for All Nations, 2014)
As the world battles the deadly Ebola virus, the experience of Dr. Ada Igonoth offers hope and encourages the faith of others to believe God for healing.